Pill power: The prequel - Lena Edlund; Cecilia Machado (Institute for the Study of Labor (IZA), 2011)
Goldin and Katz [2002], in an influential paper, argued that giving unmarried minors access to the contraceptive Pill was instrumental for women's professional advancement, because such access allowed marriage to be postponed. However, by 1960, married women could get the Pill and thence it is not clear why early marriage would interfere with the pursuit of professional interests. We explore the effects of this alternative, earlier, and common, route to the Pill. Using variation in state minimum-age marriage laws (EMA), we find that EMA precipitated marriage, delayed fertility within marriage, and improved the educational and occupational outcomes of women, especially non-college women. Thus, fertility control, marriage notwithstanding, emerges as a key enabler of women's educational and professional advancement.
urn:nbn:de:101:1-201104113415
Keywords: J13; J24; 330; contraceptive pill; marriage; education; occupation; Empfängnisverhütungsmittel; Wirkungsanalyse; Ehe; Frauenbildung; Frauenerwerbstätigkeit; Erwerbsverlauf; Schätzung; USA